Betelvine (Piper betle L.): A comprehensive insight into its ethnopharmacology, phytochemistry, and pharmacological, biomedical and therapeutic attributes. Issue 11 (2nd May 2022) - Biswas, Protha; Anand, Uttpal; Saha, Suchismita Chatterjee; Kant, Nishi; Mishra, Tulika; Masih, Harison; Bar, Ananya; Pandey, Devendra Kumar; Jha, Niraj Kumar; Majumder, Madhumita; Das, Neela; Gadekar, Vijaykumar Shivaji; et al.
Abstract: Piper betle L. (synonym: Piper betel Blanco), or betel vine, an economically and medicinally important cash crop, belongs to the family Piperaceae, often known as the green gold. The plant can be found all over the world and is cultivatedprimarily in South East Asian countries for its beautiful glossy heart‐shaped leaves, which are chewed or consumed as betelquidand widely used in Chinese and Indian folk medicine, as carminative, stimulant, astringent, against parasitic worms, conjunctivitis, rheumatism, wound, etc., andis also used for religious purposes. Hydroxychavicol is the most important bioactive compound among the wide range of phytoconstituents found in essential oil and extracts. The pharmacological attributes of P . betle are antiproliferation, anticancer, neuropharmacological, analgesic, antioxidant, antiulcerogenic, hepatoprotective, antifertility, antibacterial, antifungal and many more. Immense attention has been paid to nanoformulations and their applications. The application of P . betle did not show cytotoxicity in preclinical experiments, suggesting that it could serve as a promising therapeutic candidate for different diseases. The present review comprehensively summarizes the botanical description, geographical distribution, economic value and cultivation, ethnobotanical uses, preclinical pharmacological properties with insights of toxicological, clinical efficacy, and safety of P . betle . The findings suggest that P . betle represents an orally active and safe natural agent that exhibits great therapeutic potential for managing various human medical conditions. However, further research is needed to elucidate its underlying molecular mechanisms of action, clinical aspects, structure–activity relationships, bioavailability and synergistic interactions with other drugs.